An Alternative Testable Form of the Consumption CAPM - Kazemi, Hossein B. (Journal of Finance, 1988)
This paper develops a consumption-oriented model of asset prices in a multigood economy that is, in principle, testable even when aggregate consumption of goods and their market prices are only partially observable. Previous studies show that, when there are m consumption goods, equilibrium expected excess returns on securities are functions of their covariances with m + 1 variables—aggregate consumption expenditure and market prices of consumption goods. Without making any further assumptions, the present model shows that a similar equilibrium relationship can be expressed in terms of covariances of asset returns with the following m + 1 variables: market prices of k consumption goods and aggregate consumption of m + 1 − k goods. Because the author's result provides researchers with some flexibility in choosing the set of m + 1 variables that measure riskiness of securities, it should lead to more powerful tests of the model.